Latent Cytomegalovirus (CMV) Infection Does Not Detrimentally Alter T Cell Responses in the Healthy Old, But Increased Latent CMV Carriage Is Related to Expanded CMV-Specific T Cells - Jackson, Sarah E.; Sedikides, George X.; Okecha, Georgina; Poole, Emma L.; Sinclair, John H.; Wills, Mark R. (Frontiers in Immunology, 2017)
Human cytomegalovirus (HCMV) primary infection and periodic re-activation of latent virus is generally well controlled by T-cell responses in healthy people. In older donors, overt HCMV disease is not generally seen despite the association of HCMV infection with increased risk of mortality. However, increases in HCMV-DNA in urine of older people suggest that, although the immune response retains functionality, immunomodulation of the immune response due to lifelong viral carriage may alter its efficacy. Viral transcription is limited during latency to a handful of viral genes and there is both an IFNγ and cellular IL-10 CD4+ T-cell response to HCMV latency-associated proteins. Production of cIL-10 by HCMV-specific CD4+ T-cells is a candidate for ageing related immunomodulation. To address whether long-term carriage of HCMV changes the balance of cIL-10 and IFNγ secreting T-cell populations, we recruited a large donor cohort aged 23–78 years and correlated T-cell responses to 11 HCMV proteins with age, HCMV-IgG levels, latent HCMV-load in CD14+ monocytes and T-cell numbers in the blood. IFNγ responses by CD4+ and CD8+ T-cells to all HCMV proteins were detected, with no age-related increase in this cohort. IL-10 secreting CD4+ T cell responses were predominantly to latency-associated proteins but did not increase with age. Quantification of HCMV genomes in CD14+ monocytes, a known site of latent HCMV carriage, did not reveal any increase in viral genome copies in older donors. Importantly, there was a significant positive correlation between the latent viral genome copy number and the breadth and magnitude of the IFNγ T-cell response to HCMV proteins. This study suggests in healthy aged donors that HCMV specific changes in the T cell compartment were not effected by age and were effective, as viremia was a very rare event. Evidence from studies of unwell aged has shown HCMV to be an important co-morbidity factor, surveillance of latent HCMV load and low-level viremia in blood and body fluids, alongside typical immunological measures and assessment of the anti-viral capacity of the HCMV-specific immune cell function would be informative in determining if anti-viral treatment of HCMV replication in the old maybe beneficial.